INFLUENCER'S ATTRACTIVENESS AND TRUSTWORTHINESS AS PREDICTORS OF PURCHASE INTENTION FOR BODY LOTION PRODUCTS: THE MEDIATING ROLE OF BRAND TRUST AMONG SOCIAL MEDIA USERS - Yessi Fadhilla; Ferry Setiawan; Titis Purwaningrum; Eka Destriyanto Pristi Ayuningtyas (STABILITY : Journal of Management and Business, 2026)
The rapid growth of social media has increased the use of influencer marketing in shaping consumer purchasing behavior. Grounded in the Stimulus-Organism-Response (S-O-R) Theory, this study examines the effects of Influencer's Attractiveness and Influencer's Trustworthiness on Purchase Intention through Brand Trust as a mediating variable. A quantitative approach was employed using purposive sampling of 100 Management students at Universitas Muhammadiyah Ponorogo. Data were collected through questionnaires and analyzed using SEM-PLS with SmartPLS 4. The results show that Influencer's Attractiveness and Influencer's Trustworthiness positively affect Brand Trust. Influencer's Trustworthiness and Brand Trust significantly influence Purchase Intention, while Influencer's Attractiveness has no direct effect on Purchase Intention. Brand Trust also mediates the relationship between influencer characteristics and Purchase Intention. These findings imply that trustworthy and attractive influencers can strengthen brand trust and increase consumers' purchase intention